147k views
3 votes
Select the correct answer from the drop-down menu.

Find the trinomial.
(a^2- 6) and (a^2+ 4) are the factors of

a^4 + 2a^2 + 24
a^4 - 2a^2 - 24
a^4 + 2a^2 - 24
a^4 - 2a^2 +24

1 Answer

3 votes

Answer:


a^4 -2a^2 -24

Explanation:

Given


(a^2- 6) \ and\ (a^2+ 4)

Required

Find the trinomial

Let T represents the trinomial;

To calculate the trinomial, we simply multiply the above factors;

This done as follows;


T = (a^2 - 6)(a^2 +4)

Expand


T = a^2(a^2 +4) -6(a^2 +4)

Open bracket


T = a^2*a^2 +a^2*4 -6*a^2 -6 * 4


T = a^4 +4a^2 -6a^2 -24


T = a^4 -2a^2 -24

The above can not be solved any further; hence, the trinomial is
a^4 -2a^2 -24

User Hypnovirus
by
4.3k points